2020
DOI: 10.1038/s41598-020-78864-4
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular role of IL-6 in mesenchymal stromal cell immunosuppression and proliferation

Abstract: Interleukin (IL)-6 is a pleiotropic cytokine involved in the regulation of hematological and immune responses. IL-6 is secreted chiefly by stromal cells, but little is known about its precise role in the homeostasis of human mesenchymal stromal cells (hMSCs) and the role it may play in hMSC-mediated immunoregulation. We studied the role of IL-6 in the biology of bone marrow derived hMSC in vitro by silencing its expression using short hairpin RNA targeting. Our results show that IL-6 is involved in immunosuppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 41 publications
0
43
1
1
Order By: Relevance
“…In particular, in human BM-MSCs, TNF-α induces the expression of ICAM-1 after 6 h of exposure, reaching the highest levels at 24 and 48 h [107]; this event is associated with a greater migratory capacity [140]. Likewise, at 24 h, treatment with TNF-α increases the levels of VCAM-1 [141], vascular endothelial growth factor (VEGF), insulin-like growth factor 1 (IGF-1), and HGF [142,143], while at 48 h, significantly higher levels of IL-6 are detected [16].…”
Section: Effects Of Tnf-α and Ifn-γ On The Expression Of Immunoregulatory Molecules By Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in human BM-MSCs, TNF-α induces the expression of ICAM-1 after 6 h of exposure, reaching the highest levels at 24 and 48 h [107]; this event is associated with a greater migratory capacity [140]. Likewise, at 24 h, treatment with TNF-α increases the levels of VCAM-1 [141], vascular endothelial growth factor (VEGF), insulin-like growth factor 1 (IGF-1), and HGF [142,143], while at 48 h, significantly higher levels of IL-6 are detected [16].…”
Section: Effects Of Tnf-α and Ifn-γ On The Expression Of Immunoregulatory Molecules By Mscsmentioning
confidence: 99%
“…Therefore, only a general overview of these mechanisms is provided here. The molecules involved in these processes include prostaglandin E2 (PGE2), transform-ing growth factor-beta (TGF-β), tumor necrosis factor-stimulated gene-6 (TSG-6), hepatocyte growth factor (HGF), human leukocyte antigen-G5 (HLA-G5), IL-6, IL-10, and galectins [5,6,[16][17][18]. These mechanisms also include the effects on the microenvironment induced by the intracellular enzymes indoleamine-2,3-dioxygenase (IDO) and inducible nitric oxide synthase (iNOS) [10,19,20], as well as the production of adenosine by the ectonucleotidase CD73 [21] (Figure 1).…”
Section: Immunoregulation Mediated By Secreted Factorsmentioning
confidence: 99%
“…MSCs can secrete anti-inflammatory cytokines such as indoleamine-pyrrole 2,3-dioxygenase and prostaglandin E2, as well as pro-inflammatory cytokines such as IL-6 and TNF-α ( 69 ), which may accelerate disease progression. Another study revealed that IL-6 silencing could weaken the inhibition of the proliferation of activated T cells ( 95 ). Therefore, MSCs may have dual effects on the disease.…”
Section: Potential Causes Of Msc Therapy Inefficacy In Sle Treatmentmentioning
confidence: 99%
“…On activation of cytokine receptors, the MSCs are able to modify the cytokine and chemokine profile in the environment through production of additional factors. 131 Thus, it is likely that MSCs in both the endosteal and perivascular niche activate inflammatory programs during chronic alcohol consumption, which may directly affect the maturation of neighboring HSPCs. However, this remains hypothetical and future studies are needed to address whether the cellular components of the HSC niches adapt their hematopoiesis-supporting functions according to the inflammatory status of the BM, and whether such changes are persistent or reversible during an abstinent period.…”
Section: Lifestyle Factors and Their Influence On Hsc Nichesmentioning
confidence: 99%